Gar ned krank is a ned g’sund - Müller, Wilfried; Mann, Klaus (DMW - Deutsche Medizinische Wochenschrift, 2018)
This article is written in remembrance of Karl Valentin’s 70th anniversary of his death. He was a comedian and song writer suffering from vegetative dystonia and depression lifelong. This hypochondriac developed extreme self observation and had anxiety to get ill permanently. As one year old, his brother died of diphteria and he was close to death himself. After jumping in an ice cold river in Munich as a young man he caught a pneumonia. From that day he had a undefined long lasting lung disease. His performances and pieces of literature in Bavarian dialect are characterized by critical thoughts about the world in general and human vulnerability including his own in a philosophical way. His sarcastic view of the world, which was rarely pleasant for the counterpart still induced admiration of many audiences and was satisfying for Karl Valentin’s egocentrism. He has been the most famous Bavarian comedian during world war II and during the early days of the Republic of Germany.
Keywords: Karl Valentin; Komödiant; Krankheit; Hypochonder; Depression; Sarkasmus; Egozentrizität